Parameter space of Morse oscillator - Yang, T. Min; M. S., Nurisya (Malaysian Institute of Physics, 2023)
We present an analysis of the mathematical structure of SU(2) group, specifically the commutation relation between the raising and lowering operators of the Morse oscillator. The connection between the commutator of operators and the parameters of a Morse oscillator is investigated. We show that the changes in parameter are important in the construction of the commutation relation. The parameter space of the Morse oscillator is visualized to scrutinize the mathematical relations that are related to the Morse oscillator. This parameter space is the space of possible parameter values that depend on the depth of the Morse potential well and other parameters. We discuss the plots of the parameter space in detail. The algorithm that we present is reliable to a large extent. It is also applicable to other quantum systems with certain modifications.